Syrup to no good - Bruns, Catherine (Bruns, Catherine. Maple Syrup mystery, 2023)
"Spring has finally come to Sugar Ridge, Vermont, and with it the end of syrup-making season. But Leila Khoury, new owner of Sappy Endings Farm, won't be making like molasses any time soon. Her best friend Heather's wedding is coming up, and Leila will do anything to make sure it lives up to all her sweetest dreams. Even with Leila's own romantic past stirring up trouble, everything is going to plan until the bridal shower ends up with a body count. Heather's rich and backstabbing aunt had a whole orchard of enemies, so Leila will have her work cut out for her. Can she tap the killer before Heather's dream wedding becomes a nightmare? Includes delicious Middle Eastern recipes!"--